KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBANGUN KOMUNIKASI DAN PARTISIPASI GURU DI SMP TERPADU DARUL MUTTAQIN SURABAYA - Najwa Akmalia Ramadhani; Risna Andara Kusuma; Galih Rachmad Pratama; Maharani Desita Eka Cahyani; Dian Ramadhani; Likfatmawati Maslakah; Ayasha Nabila Audya Nency; Erny Roesminingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the leadership system of the principal at SMP Terpadu Darul Muttaqien based on Likert’s leadership theory in fostering effective communication and enhancing teacher participation. The study employs a qualitative-descriptive approach, focusing on the principal’s communication patterns, the level of teacher engagement, working relationships among school community members, and barriers to policy implementation. The research findings indicate that school principals’ leadership styles tend to follow a consultative approach that is beginning to shift toward a participatory approach. School principals practice clear and open communication and involve teachers in the decision-making process. Teachers are also given the opportunity to express their opinions, criticisms, and suggestions regarding various school activities. The working relationships that have been established are collaborative and foster a conducive organizational climate. However, there are still challenges in the form of differences in teachers’ understanding of the information provided, resulting in policy implementation that is not yet fully consistent. From a Likert perspective, the principal’s leadership has moved toward a participatory system, but strategic decisions are still dominated by the principal. Therefore, it is necessary to strengthen feedback-based communication and enhance collaboration in order to optimize teacher participation.